Last Stand of the Louisiana Shrimpers - Lirette, Emma Christopher (Book collections on Project MUSE., 2022)
"In recent years, shrimpers on the Louisiana coast have faced a historically dire shrimp season, with the price of shrimp barely high enough to justify trawling. Yet, many of them wouldn't consider leaving shrimping behind, despite having transferrable skills that could land them jobs in the oil and gas industry. Since 2001, shrimpers have faced increasing challenges to their trade: an influx of shrimp from southeast Asia, several traumatic hurricane seasons, and the largest oil spill at sea in American history. In Last Stand of the Louisiana Shrimpers, author Emma Christopher Lirette traces how Louisiana Gulf Coast shrimpers negotiate land and blood, sea and freedom, and economic security and networks of control. This book explores what ties shrimpers to their boats and nets. Despite feeling trapped by finances and circumstances, they have created a world in which they have agency. Lirette provides a richly textured view of the shrimpers of Terrebonne Parish, Louisiana, calling upon ethnographic fieldwork, archival research, interdisciplinary scholarship, and critical theory. With evocative, lyrical prose, she argues that in persisting to trawl in places that increasingly restrict their way of life, shrimpers build fragile, quietly defiant worlds, adapting to a constantly changing environment. In these flickering worlds, shrimpers reimagine what it means to work and what it means to make a living"--